Enhancing Thermal Performance Investigations of a Methane-Fueled Planar Micro-Combustor with a Counter-Flow Flame Configuration - Liaoliao Li; Yuze Sun; Xinyu Huang; Lixian Guo; Xinyu Zhao (Energies)
To enhance the performance of combustors in micro thermophotovoltaic systems, this study employs numerical simulations to investigate a planar microscale combustor featuring a counter-flow flame configuration. The analysis begins with an evaluation of the effects of (1) equivalence ratio Φ and (2) inlet flow rate Vi on key thermal and combustion parameters, including the average temperature of the combustor main wall (<semantics><mover accent="true">T¯</mover>w</semantics>), wall temperature non-uniformity (<semantics><mover accent="true">R¯</mover>Tw</semantics>) and radiation efficiency (<semantics>ηr</semantics>). The findings indicate that increasing Φ causes these parameters to initially increase and subsequently decrease. Similarly, increasing the inlet flow rate leads to a monotonic decline in <semantics>ηr</semantics>, while the <semantics><mover accent="true">T¯</mover>w</semantics> and <semantics><mover accent="true">R¯</mover>Tw</semantics> exhibit a rise-then-fall trend. A comparative study between the proposed combustor and a conventional planar combustor reveals that, under identical inlet flow rate and equivalence ratio conditions, the use of the counterflow flame configuration can increase the <semantics><mover accent="true">T¯</mover>w</semantics> while reducing the <semantics><mover accent="true">R¯</mover>Tw</semantics>. The Nusselt number analysis shows that the counter-flow flame configuration micro-combustor achieves a larger area with positive Nusselt numbers and higher average Nusselt numbers, which highlights improved heat transfer from the fluid to the solid. Furthermore, the comparison of blow-off limits shows that the combustor with counter-flow flame configuration exhibits superior flame stability and a broader flammability range. Overall, this study provides a preliminary investigation into the use of counter-flow flame configurations in microscale combustors.